European Tort Law Yearbook (De Gruyter, 2009)
The European Tort Law Yearbook provides a comprehensive overview of the latest developments in tort law in Europe. It contains reports on most EU Member States alongside contributions from Norway and Switzerland. An overview of developments in the field of EU law is also provided.